Transposon-mediated telomere destabilization: a driver of genome evolution in the blast fungus. Issue 13 (19th June 2020) - Rahnama, Mostafa; Novikova, Olga; Starnes, John H; Zhang, Shouan; Chen, Li; Farman, Mark L
Abstract: The fungus Magnaporthe oryzae causes devastating diseases of crops, including rice and wheat, and in various grasses. Strains from ryegrasses have highly unstable chromosome ends that undergo frequent rearrangements, and this has been associated with the presence of retrotransposons ( Magnaporthe oryzae Telomeric Retrotransposons—MoTeRs) inserted in the telomeres. The objective of the present study was to determine the mechanisms by which MoTeRs promote telomere instability. Targeted cloning, mapping, and sequencing of parental and novel telomeric restriction fragments (TRFs), along with MinION sequencing of genomic DNA allowed us to document the precise molecular alterations underlying 109 newly-formed TRFs. These included truncations of subterminal rDNA sequences; acquisition of MoTeR insertions by 'plain' telomeres; insertion of the MAGGY retrotransposons into MoTeR arrays; MoTeR-independent expansion and contraction of subtelomeric tandem repeats; and a variety of rearrangements initiated through breaks in interstitial telomere tracts that are generated during MoTeR integration. Overall, we estimate that alterations occurred in approximately sixty percent of chromosomes (one in three telomeres) analyzed. Most importantly, we describe an entirely new mechanism by which transposons can promote genomic alterations at exceptionally high frequencies, and in a manner that can promote genome evolution while minimizing collateral damage to overall chromosome architecture and function.